PENGEMBANGAN MEDIA RODA CALISTA (MEMBACA DAN MENULIS KATA) UNTUK MENINGKATKAN LITERASI SISWA KELAS 1 SD N MEJING 2 YOGYAKARTA - Indah Mah Bengi; Arip Febrianto (STKIP Subang, 2026)
The purpoise of thiis stuidy wais to devielop a learining media called Cialista Wheiel (Reading and Writing Wiords) to impirove the literacy sikills of first-girade studentsi at SDN Mejing i2 Yogyakartia. The methodi used was Researchi and Developiment (R&D) with ithe ADDIE model, whiich includes analiysis, design, deivelopment, implemientation, and evaluatiion stages. Diata were collectied through observiation, interviews, qiuestionnaires, and tests, and analyzeid based on feasibiility, practiicality, effeictiveness, and statistiical tests (noirmality, homogeneiity, and hypothesisi testing). The resulits showed thait the media wias feasible, witih a score of 75.5i% from media experits and 87.5% from matierial experts. The practiciality test shoiwed very high results, wiith teacher responises at 90.6% andi student responsies at 97.8%. The data weire normally distriibuted and homogenieous. Furthermorie, the indepeindent sample t-test sihowed a signifiicance value iof 0.009 < 0.05, indiicating a signiificant effect of the Cailista Wheel meidia on studients' literaicy skills. The effiectivieness test also showedi an improvementi in students' iliteracy scores from a preteist average of 46.42 to a posittest averagie of 85.89, with an incriease of 39.47. Thus, the Caliista Wheel leairning media is valid, practical, and effecitive in imprioving studeints' liteiracy skills.